Personal and Contextual Factors as Correlates of Entrepreneurial Intentions among Pre-service Science, Technology, and Mathematics Teachers - Adeneye Olarewaju A. Awofala; Oladiran S. Olabiyi; Omolabake T. Ojo; Adenike J. Oladipo; Alfred O. Fatade; Uchenna N. Udeani (ASEAN Journal of Science and Engineering Education, 2023)
This study through a quantitative paradigm investigated personal and contextual factors as correlates of entrepreneurial intention among 1120 pre-service science, technology, and mathematics teachers. The results showed that personal factors (need for achievement, internal locus of control, risk-taking propensity, and creativity) and contextual factors (perceived structural support, perceived educational support, and perceived relational support) contributed 84.1% to the prediction of entrepreneurial intention among participants. The entrepreneurial intention of pre-service science, technology, and mathematics teachers had a positive correlation with each dimension of personal and contextual factors. In line with these results, both personal (need for achievement, internal locus of control, risk-taking propensity, and creativity) and contextual (perceived structural support, perceived educational support, and perceived relational support) factors be strengthened in pre-service science, technology, and mathematics teachers’ preparation university.